2015
DOI: 10.1021/jp511448e
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Dynamics and Sequence Dependence of DNA and RNA Binding to Single Walled Carbon Nanotubes

Abstract: Noncovalent polymer-single walled carbon nanotube (SWCNT) conjugates have gained recent interest due to their prevalent use as electrochemical and optical sensors, SWCNT-based therapeutics, and for SWCNT separation. However, little is known about the effects of polymer-SWCNT molecular interactions on functional properties of these conjugates. In this work, we show that SWCNT complexed with related polynucleotide polymers (DNA, RNA) have dramatically different fluorescence stability. Surprisingly, we find a dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 58 publications
(127 reference statements)
2
85
0
Order By: Relevance
“…Recently, Landry et al reported that RNA-wrapped SWNTs slowly equilibrated upon dilution in PBS, as manifested by a gradual fluorescence modulation over several hours [36], whereas DNA wrappings showed a much more stable fluorescence signal after dilution. Although 23 of the 24 sequences used in this study were DNA, many sequences were much shorter than the 30-mer oligonucleotides used in the previous work and may not bind as tightly.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Landry et al reported that RNA-wrapped SWNTs slowly equilibrated upon dilution in PBS, as manifested by a gradual fluorescence modulation over several hours [36], whereas DNA wrappings showed a much more stable fluorescence signal after dilution. Although 23 of the 24 sequences used in this study were DNA, many sequences were much shorter than the 30-mer oligonucleotides used in the previous work and may not bind as tightly.…”
Section: Resultsmentioning
confidence: 99%
“…Single walled carbon nanotubes dispersion can be assisted by surfactants like sodium dodecyl sulfate (SDS) or sodium cholate (SC) [38], DNA or RNA [39,40] or other amphiphilic copolymers [27]. Tsai and co-workers, for example, immobilized glucose oxidase (GOx) onto SWCNTs and determined that the enzyme retained 75% of its activity upon adsorption.…”
Section: Non-covalent Immobilizationmentioning
confidence: 99%
“…However, there is lack of, and need for, a systematic and predictable understanding of the parameters that determine protein-SWCNT fates in their interactions with biological systems. Advances in experimental and theoretical tools to study SWCNTbiomolecule conjugate systems at the molecular scale [37,40,87] have emerged, but many remain to be extended for molecularscale SWCNT-protein studies. The risk of CNPs triggering an immune response should be also considered, since the protein components of the complement system can bind to carbon nanotubes.…”
Section: Toxicity Of Delivered Swcnt-protein Conjugatesmentioning
confidence: 99%
“…59 Landry and co-workers have extended this platform to study ribonucleic acid (RNA) contributions to fluorescence response. 72 Recent experimental measurements suggest that the differences in (GU) 15 -RNA and (GT) 15 -DNA conformations have a significant impact on fluorescence response. A comparison of both polymers shows that the (GU) 15 -RNA has a lower conformational stability on the SWCNT than the corresponding DNA-based complex.…”
Section: Engineering Sensor Selectivity Of Nir Fluorescence Sensors Bmentioning
confidence: 99%